2016
DOI: 10.1016/j.biomaterials.2015.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin encapsulated in stealth liposomes conferred with light-triggered drug release

Abstract: Stealth liposomes can be used to extend the blood circulation time of encapsulated therapeutics. Inclusion of 2 molar % porphyrin-phospholipid (PoP) imparted optimal near infrared (NIR) light-triggered release of doxorubicin (Dox) from conventional sterically stabilized stealth liposomes. The type and amount of PoP affected drug loading, serum stability and drug release induced by NIR light. Cholesterol and PEGylation were required for Dox loading, but slowed light-triggered release. Dox in stealth PoP liposom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
166
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 204 publications
(171 citation statements)
references
References 56 publications
4
166
1
Order By: Relevance
“…To address this, PoP liposomes comprising of Pyro‐lipid rather than HPPH‐lipid were developed 209. A 2 mol.% quantity of Pyro‐lipid imparted the light‐triggered capability of conventional liposomes, while 5 mol.% PEG‐lipid enable the long circulation of Dox‐loaded PoP liposomes (Dox‐PoP liposomes).…”
Section: Nanoparticle‐mediated Cptmentioning
confidence: 99%
“…To address this, PoP liposomes comprising of Pyro‐lipid rather than HPPH‐lipid were developed 209. A 2 mol.% quantity of Pyro‐lipid imparted the light‐triggered capability of conventional liposomes, while 5 mol.% PEG‐lipid enable the long circulation of Dox‐loaded PoP liposomes (Dox‐PoP liposomes).…”
Section: Nanoparticle‐mediated Cptmentioning
confidence: 99%
“…For instance, a NIR lighttriggered membrane permeabilization phenomena [15 ] has been achieved in long-circulating liposomal doxorubicin formulations with the modest titration of HPPHlipid [15 ,35] or Pyro-lipid [36] into those formulations. It was reported that the inclusion of as little as 5-10 mol.% HPPH-lipid or 2 mol.% Pyro-lipid was needed for the spatially and temporally controlled release of entrapped doxorubicin with laser irradiation in vivo [35,36].…”
Section: The Formulation -Ex Vivo Self-assembling Porphysomesmentioning
confidence: 99%
“…The stimuli-sensitive nanocarriers maintain their stealth function throughout circulation, and upon arrival at the specific tumor site, undergo rapid changes, such as aggregation, disruption, and permeability changes, which trigger drug release when exposed to a particular tumor microenvironment [2,52,53]. In order to achieve site-specific triggered drug release, several strategies have been investigated, for example, internal stimuli that are characteristic for a tumor microenvironment (low pH, redox potential, high temperature, and enzymes) and external stimuli, such as magnetic fields, ultrasound, or light [54][55][56]. Both internal and external stimuli-sensitive liposomes will be addressed further, classified according to the mechanism exploited.…”
Section: Stimuli-sensitive Liposomesmentioning
confidence: 99%